Evaluation and Application of an Engineering Calculation Method of the Static Performance of an Aerostatic Journal Bearing with Multiple Orifice-Type Restrictors - Yangong Wu; Zheng Qiao; Wentao Chen; Jiadai Xue; Bo Wang (Lubricants, 2022)
A simplified calculation method is evaluated to calculate the static performance of an aerostatic journal bearing with multiple orifice-type restrictors. This method adopts a one-dimension flow assumption and is a fast calculation method to design journal bearings in engineering by directly linking the structural parameters and performance parameters affecting radial bearings with nonlinear equations. In addition, this method is verified with computational fluid dynamics by two actual case studies, and it is found that the LCC difference between those two methods is less than 5% for a 200 mm diameter spindle, and less than 10% for a 100 mm diameter spindle. Subsequently, the influence of a key parameter<semantics><mtext> </mtext>ζi<mtext> </mtext></semantics>on the static performance of journal bearings is explained theoretically. This method is much easier and more intuitive compared with numerical computational methods. Furthermore, it promotes the application of aerostatic journal bearings.